Controle motor em pacientes com doença de Parkinson: terapia do espelho, foco de atenção e tarefa dupla - Lahr, Juliana [UNESP] (2015)
Background: Parkinson’s disease (PD) presents asymmetric early motor symptoms, and those symptoms affect the processing and the integration of proprioceptive information. Due to that, the upper limb motor control is impaired even on single task (isolated manual task) and dual task (manual task and posture control). Because these sort of tasks are performed during activities of daily living, the role of asymmetry on those task must be clarified to elucidate the effects of disease on PD functionality and thus guide the therapists choose more effective interventions. Among strategies of intervention on PD motor impairments, two strategies that deserve special attention are the instruction of external focus of attention and mirror therapy (MT). Both interventions might be potentially effective to facilitate motor learning. Aims: to assess the role of PD asymmetry on upper limbs motor control and postural control in conditions of single versus dual task; and tasks with attentional focus with instructions versus external focus as well as to verify the effect of MT on upper limbs motor control more affected on postural control of PD patients. Methods: Twenty PD patients were submitted to assessments on: Upper Limb motor control (kinematic analysis) and postural control (kinetics analysis), in single and dual task conditions, with and without external focus of attention. Posteriorly, the subjects were distributed in two different groups: GI1 and GI2. The MT protocol consisted in a unilateral home therapy on less affected upper limb, performed 30 minutes a day, five days a week, during 6 consecutives weeks. To assist the subjects of GI1, they performed this protocol using a visual feedback (mirror therapy). Both groups were assessed before and after therapy protocol. Results: performance was not different between upper limbs and single and dual tasks, both in single and in dual task. After protocol period, both groups showed improvements on kinematic outcomes (manual dexterity, movement frequency of the hand, hesitation and task performance time improvements, independent of the sort of focus of attention that was used). Conclusion: Manual task is not affected by PD asymmetry on single and dual task. The external focus of attention was not effective to improve the task performance in PD patients, and it is not recommended to be performed during dynamic tasks. The therapy protocol with or without visual feedback promotes extended benefits on execution and planning of manual task of more affected upper limb independently of focus of attention, but it is not able to decrease the functional and motor impairments neither improve postural control. Therefore MT seems to be equally effective on manual tasks benefits, however more studies are necessary to confirm this efficacy.